Body weight change during the first year of HEMODIALYSIS is influenced by the dry weight quest - Charles Chazot; Patrik Deleaval; Anne-Lise Bernollin; Cyril Vo-Van; Guillaume Jean (The Korean Society of Nephrology, 2012)
Fluid overload, high blood pressure (BP) and nutrition disturbances may improve after HD onset. However HD patients remain exposed to a high risk of death. We report the relationship between the dry weight quest and nutritional markers on the survival in incident HD patients. Among a cohort including 308 patients stating HD therapy 251 (age=65,8±14,8 y.o.; F/M=93/158; diabetes=36%) survived at least one year after dialysis onset and were followed for an average of 44,9 months. During the first 8 weeks, the prescribed BW decreased by 6.5±5.6% and then started to increase again. From Week 8 (W8) to W52, the BW change (Δ) was+1,9±7,4% (extremes:-24,6 to+28,2%). Serum albumin and nPNA changed respectively by+7.8 and+11.4%. (+7.6% vs-3.6%, p=0.0001). The initial W8-W1 BW Δ (expressed as % of the BW at HD onset) was significantly correlated with the systolic BP Δ at W26 and W52 (respectively p=0.0007 and 0.0033). It was also inversely correlated with the Δ in serum albumin and nPNA (p=0.002 and 0.04) but not with BW Δ between W8 and W52. The W52W8-BW Δ and the W52-W1-systolic BP Δ were significantly correlated (r=-0,14, p=0.03). When the patients were split in two groups according the median of systolic BP change (-20.8 vs +7.8%), the W52W8 BW Δ was significantly higher in the group of the larger systolic BP decrease (+3.3 vs +0.6%, p=0.004). Hence weight gain during the first year of HD treatment that is a strong predictor of survival in our experience (reported in another abstract) is influenced by the dry weight quest. In our practice, the systolic BP decrease is related to fluid removal and is associated with better patient survival, opposite to the reverse epidemiology concept. Further studies using bioimpedance are necessary to confirm that an optimal fluid status may improve the nutritional status in HD patients.